Toxicity of dietary Heliotropium dolosum seed to mice - Eröksüz, Y; Eröksüz, H; Özer, H; Sener, B; Tosun, F; Akyüz, Ç (Comparative Toxicology Lab, 2001)
Experimental pyrrolizidine alkaloid intoxication was produced in inbred Swiss mice. Animals were fed diets containing 0, 1, 3, 5, or 10% Heliotropium dolosum seed for 24 w. The seeds contained 0.13% total alkaloid concentration composed of 4 specific components: lasiocarpine (78.79%) heliosupine (11.96%). echimidine (5.43%), and heliotrine (3.82%). Deaths occurred in all dosed groups and increased with dietary seed concentration. Massive to submassive liver necrosis together with sinusoidal congestion, and hemorrhage or multifocal hepatocytic necrosis was limited to animals which survived <5 w and were fed on 10% seed. Moderate to severe hepatomegalocytosis, scattered single cell necrosis, and mild subcapsuler fibrosis were seen in all test group animals that survived > 5 w. Intranuclear eosinophilic inclusions in hepatocytes and bile duct and ductular cell hyperplasia were the most noticeable lesions in the 1,3, and 5% groups. There was mild to moderate renal tubular megalocytosis in the 3, 5, and 10% groups. It seems likely that H dolosum seed, at least to a limited extent, constitutes a health hazard for certain animal species.
Keywords: Pyrrolizidine Alkaloids; Rats